VD_FINDINFO AVS 42/21 - 54/2021 vom 10. November 2021 - VD Tribunal cantonal (2021)
DÉCISION D'IRRECEVABILITÉ, RESPONSABILITÉ DE L'EMPLOYEURAVS, SIÈGE | 52 al. 1 LAVS, 52 al. 5 LAVS, 94 al. 1 let. d LPA-VD